PELATIHAN SERVIS RINGAN KENDARAAN SEPEDA MOTOR BAGI MASYARAKAT DESA RIDOGALIH - Dear, Muhamad; Ekawati, Fatimah Dian; Supratno, Setyo (An-Nizam, 2024)
Motorbikes are a means of transportation that is often used in daily activities, the development of increasingly sophisticated technology has begun to be combined with the help of electronic control circuits such as injection systems to control combustion in the motorcycle combustion chamber or indicators to show hot engine temperatures that make it easier for motorcycle owners to carry out vehicle maintenance. Therefore, due to the lack of workshops or vehicle service services, here the author will share information about motorcycle maintenance that can be done by yourself to save costs and can be developed as a form of business, such as a workshop. With this lack of information, most people only use motorbikes for their daily needs and ignore motorcycle maintenance. Here the author will educate the community on how to maintain their two-wheeled vehicles in Citeureup 1 hamlet by socializing the importance of maintaining two-wheeled vehicles, training on maintaining two-wheeled vehicles, and evaluation to ensure that the community can maintain their own motorbikes. This program also has the aim that the people of Sirnajaya Village, Serang Baru District, Bekasi Regency are able to maintain their own motorbikes and can be developed as a form of business, namely a workshop. Based on the light service training, there are several impacts, among others can increase understanding related to light service procedures such as engine oil change, axle oil, CVT maintenance and replacement of front brake lining and understand about safety riding and have understood how to drive properly.